AIAA Scitech 2021 Forum 2021
DOI: 10.2514/6.2021-1136
|View full text |Cite
|
Sign up to set email alerts
|

Piloted Simulation of Helicopter Shipboard Recovery with Visual and Control Augmentation

Abstract: Shipboard launch and recovery of helicopters continue to pose operational challenges even for experienced pilots. The factors affecting pilot workload include unsteady ship motion, the influence of ship air wakes on helicopters, insufficient visual cues, and adverse weather conditions. The goal of the current research is to investigate novel visual and control augmentation techniques and evaluate their impact on pilot workload and handling qualities for shipboard recovery operations. This paper first outlines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This objective can be reached using augmented control laws. Such control laws are particularly valuable for rotorcraft ship deck operations, which are some of the most demanding of all rotorcraft piloting tasks [1]. Assessing different levels of augmentation and determining flight control law requirements for such complex maneuvers can help to improve safety, reduce pilot effort and workload and increase the helicopter-ship operational envelope [2].…”
Section: Introductionmentioning
confidence: 99%
“…This objective can be reached using augmented control laws. Such control laws are particularly valuable for rotorcraft ship deck operations, which are some of the most demanding of all rotorcraft piloting tasks [1]. Assessing different levels of augmentation and determining flight control law requirements for such complex maneuvers can help to improve safety, reduce pilot effort and workload and increase the helicopter-ship operational envelope [2].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Reference [7] showed that inexperienced pilots could only fly a conventional helicopter when it was augmented via their H ∞ and µ controllers to offer translational rate command responses. Reference [8] showed the ability of a robust sliding mode flight controller to alleviate pilot workload for a shipboard landing task.…”
Section: Introductionmentioning
confidence: 99%
“…Such a pseudo-SMC approach, however, degrades the desirable robustness properties of the original SMC, since the linear approximation inside the boundary layer is no longer completely robust to uncertainties [13]. Pseudo-sliding mode controllers based on the boundary layer concept have been developed and studied for rotorcraft flight control applications with good results in References [8,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%